Factors in hard winter wheat affecting water absorption tolerance - Buckley, Elyse (Kansas State University, 2013)
Hard winter wheat flour is predominantly used for bread production. Optimal dough handling properties are critical in commercial bread production. Variation in flour water absorption tolerance dramatically affects dough handling. Understanding the factors which affect water absorption tolerance and the influences of genotype, environment, and their interaction on those factors will improve breeding efforts and production practices to improve the quality of bread wheat. A previous study found the γ-gliadin protein fraction correlated highly with water absorption tolerance. The objectives of this study were to confirm the effect of γ-gliadin and investigate the effects of genetics and environment on water absorption tolerance. Nineteen hard winter wheat cultivars consisting of released varieties and experimental breeding lines from the Pacific Northwest grown in 2011 in 2 locations in Oregon (Pendleton and Arlington) were obtained. Quality evaluations including flour yield, test weight, kernel weight, kernel diameter, and kernel hardness were conducted on the wheat kernels and water absorption tolerance, protein content, moisture content, ash content, Solvent Retention Capacity (SRC), starch damage, and protein composition analyses were preformed on the resulting flours. The mixograph water absorption tolerance behavior of each sample was ranked as high, medium or low. Farnum and OR2080156H grown at Arlington had the highest water absorption tolerance range (1.6mL) while Farnum, Eddy, Paladin and OR2080227H grown at Pendleton exhibited the lowest interval (0.4mL). No wheat or flour parameters measured showed high correlation with water absorption tolerance. Moderate correlation was observed between water absorption tolerance and kernel weight (r = 0.39), kernel diameter (r = 0.37), starch damage (r = 0.33), and the extractable and unextractable polymeric protein fractions (r = 0.32).
Keywords: Wheat; Water absorption; Food Science (0359)